Nonlinear conductive behavior of MoS2/PDMS composites for self-adaptive electrostatic protection - Hongfei Li; Zhaoming Qu; Yazhou Chen; Wei Cao; Kaihui Li (Polymer Testing)
Electrostatic discharge (ESD) poses a significant threat to electronic components and systems. Self-adaptive electrostatic protection materials (SAEs) are in urgent demand yet still remain a great challenge. Here, flexible and exceptional molybdenum disulfide/polydimethylsilane (MoS2/PDMS) composites were developed using a facile hybrid approach as novel ESD smart protection materials. Exceptional nonlinear conductive performance was achieved with a low volume loading of MoS2 fillers ranging from 1.08 vol% to 4.93 vol%. The composites exhibited a wide range of switching fields (Eb) from 0.65 kV/mm to 2.49 kV/mm, while the nonlinear coefficient (α) affected by potential barrier height range of 4.49 to 7.23. Mechanism analysis confirms the contribution of processes such as Ohmic behavior, Schottky emission, and F-N tunneling to the nonlinear conductivity of composites. Finite element simulations show that the increase in filler forms more conductive channels, which reduces the Eb. The electrostatic discharge experimental system designed to examine the ESD protection efficiency of MoS2/PDMS composites confirms that the composite can effectively achieve fast switching from the off state to the on state of electrostatic protection. This research is expected to be applied to reduce the risk of device damage caused by destructive high-static forces for increasingly integrated circuits.